Taxonomic revision of the genus Elmomorphus Sharp, 1888. II. Redescription of the genus and review of the species from India, Nepal, Bhutan, Myanmar, China, Thailand, Laos, Cambodia, and Vietnam (Coleoptera: Dryopidae) - Selnekovič, Dávid; Jäch, Manfred A.; Kodada, Ján (European Journal of Taxonomy, 2024)
The genus Elmomorphus Sharp, 1888 is redescribed based on morphological characters. Elmomorphus bryanti Hinton, 1935, E. montanus (Grouvelle, 1913), E. prosternalis Hinton, 1935, and E. striatellus Delève, 1968 are redescribed based on type material. Elmomorphus nepalensis Satô, 1981 is redescribed based on material collected in the vicinity of the type locality. Eighteen species of Elmomorphus were known so far world-wide, and only five species have been recorded from the study area (India, Nepal, Bhutan, Myanmar, China, Thailand, Laos, Cambodia, and Vietnam). In the present revision, 45 new species are described: E. auratus sp. nov. (China), E. auripilosus sp. nov. (Vietnam), E. bispinosus sp. nov. (China), E. calvus sp. nov. (China, Vietnam), E. catenatus sp. nov. (China), E. comosiclunis sp. nov. (China), E. corpulentus sp. nov. (China), E. cuneatus sp. nov. (Thailand), E. curvipes sp. nov. (China, Vietnam), E. dentipes Kodada, Selnekovič & Jäch sp. nov. (China, Laos, Myanmar, Thailand, Vietnam), E. depressus sp. nov. (China), E. donatus Kodada, Selnekovič & Jäch sp. nov. (China, Vietnam), E. ellipticus sp. nov. (China), E. elmoides sp. nov. (Vietnam), E. fusiformis sp. nov. (China), E. glabriclunis sp. nov. (China), E. globosus sp. nov. (China), E. hamatus sp. nov. (China), E. hongkong sp. nov. (China), E. horaki Kodada, Selnekovič & Jäch sp. nov. (Cambodia, Myanmar, Thailand), E. jendeki Kodada, Selnekovič & Jäch sp. nov. (Vietnam), E. jii sp. nov. (China), E. longitarsis sp. nov. (Thailand), E. mazzoldii sp. nov. (Thailand), E. minutus sp. nov. (China), E. oblongus sp. nov. (Vietnam), E. ovalis Kodada, Selnekovič & Jäch sp. nov. (China), E. parabrevicornis sp. nov. (China), E. paradonatus Kodada, Selnekovič & Jäch sp. nov. (China), E. paramontanus Kodada, Selnekovič & Jäch sp. nov. (China, Laos, Malaysia, Myanmar, Thailand, Vietnam), E. parvulus sp. nov. (Thailand), E. punctulatus sp. nov. (China), E. reticulatus sp. nov. (China), E. sausai Kodada, Selnekovič & Jäch sp. nov. (Vietnam), E. schillhammeri sp. nov. (China), E. schoenmanni sp. nov. (China), E. siamensis Kodada, Selnekovič & Jäch sp. nov. (Cambodia, Laos, Myanmar, Thailand, Vietnam), E. similis sp. nov. (China, Laos, Vietnam), E. simplex sp. nov. (China), E. simplipes sp. nov. (Vietnam), E. superficialis sp. nov. (China), E. sulcatus sp. nov. (China), E. umphangicus Kodada, Selnekovič & Jäch sp. nov. (Thailand), E. vietnamensis sp. nov. (Vietnam), and E. yunnanensis Kodada, Selnekovič & Jäch sp. nov. (China). The genus Elmomorphus is recorded for the first time from Bhutan, Cambodia, Myanmar, and Laos. In China (31 spp. from Anhui, Fujian, Guangdong, Guangxi, Guizhou, Hainan, Hong Kong, Hubei, Hunan, Jiangxi, Shaanxi, Yunnan, Zhejiang) and Vietnam (16 spp.), this genus is especially diverse.